Effect of chemical disinfectants and plant extracts on bacterial load in carcasses of guinea pigs (Cavia porcellus) - Sánchez V., Raúl (2015)
The aim of the study was to evaluate the effectiveness of chlorine dioxide (CD), eucalyptus leaf extract - grapefruit seed (ELE-GS), seed extract - grapefruit pulp (SE-GP) on reducing the load of aerobic mesophilic bacteria, E. coli, and total coliforms in guinea pig carcasses (Cavia porcellus). It was used a completely randomized factorial design with seven treatments: T1 = Control, T2 = CD 20 ppm, T3 = CD 30 ppm, T4 = ELE-GS 3000 ppm, T5 = ELE-GS 5000 ppm, T6 = SE-GP 400 ppm and T7 = SE-GP 800 ppm, where each treatment had five replicates (carcasses), except T1 (n=6). All treatments were effective in reducing the load of aerobic mesophilic bacteria in relation to the control group (T1). In the case ofE. coli, T5 was more efficient than T1 (p<0.05), and in total coliforms, T3, T5, T6, and T7 were more efficient that T1 (p<0.05). It is concluded that the use of CD 30 ppm and ELE-GS 5000 ppm significantly reduce the bacterial load in carcasses of guinea pigs.